PHBV/cellulose nanofibrils composites obtained by solution casting and electrospinning process - Carvalho Benini, Kelly C. C. de [UNESP]; Hilario Cioffi, Maria Odila [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP] (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2017)
In this work, nanobiocomposites of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) reinforced with cellulose nanofibrils (CNFs) were produced by electrospinning and solution casting process. CNFs were obtained by sulfuric acid hydrolysis from Imperata brasiliensis fibers. Nanocomposites loaded with 1 (wt. %) of CNFs were prepared using a mixture of solvents chloroform (CHCl3): N, N-dimethylformamide (DMF), in the ratio of 78:22 with 30 h of solubilization. Films by solution casting were obtained in a petri dish, at 50 degrees C for 1 hour, using drying casting temperature of 153 degrees C. Mats by electrospinning were obtained with a needle 20x10, drum collector rotation 27 rpm, and working distance of 10 cm. Films and mats were characterized by Scanning Electron Microscopy (SEM), X-ray diffraction (XRD) and Differential Scanning Calorimetry (DSC). It was possible to conclude that for nanobiocomposites obtained by solution casting, the addition of CNFs did not affect the transparency of the films, but provided a significant increase in the crystallization rate as observed by DSC analysis, while for electrospinning nanobiocomposites a considerable improvement in process increasing electrospinning time and quality of the mats manufactured, were observed.
Keywords: cellulose nanofibrils; PHBV; electrospinning; solution casting